SIFAT PAPAN SEMEN PARTIKEL KAYU KARET (Cement Board Property of Rubber Wood Particle) - M. Dirhamsyah (Universitas Tanjungpura, 2011)
Aim of the study was to assess the suitability of rubber wood particles in the production of cement boards. This research was conducted at the woodworkshop of the Forestry Faculty of province Tanjungpura University and the Government Polytechnic Laboratory of Pontianak. Factors examined include the use of particles of different size, namely rough particle (a1), medium particle (a2) and soft particle (a3), and using different cement qualities namely 100 % ( b1), 125 % ( b2) and 150 % ( b3). The properties of cement board particles tested included the physic properties (water quality and density) and mechanic properties (firmness of static refraction (MOR) and thickness reduction caused by 3 kg / cm surface pressure). The test result were compared to the standard of DIN 1101. The gathered data were analyzed using the factorial trial method with complete random model (RAL) and 3 (three) repetitions. The best results were adieved by combining soft particles with 150 % cement quality. The use of roughs Particles and 125 % cement quality produced the best density value. while the use of soft particles and 150 % cement quality produced best results regarding water quality, firmness of static refraction (MOR) and thickness reduction caused by 3 kg / cm surface pressure. Keywords: Rubber wood, Size Particle, cement quality, cement board particle